Mainland China Student Study in Taiwan: Motivation, Impression, Potential Political Reform Agent - Harryanto Aryodiguno; Tiara Cornelia (AEGIS : Journal of International Relations, 2022)
Since opened in 2011, the number of Chinese students goes to Taiwan for 6 months exchange grew more and more every year. What things that motivate the Chinese student to come to Taiwan? Is it related to the current both country’s political condition? What they been thinking about Taiwan, before and after they came? Will they obtain a new perspective about cross-strait disputes? Will they be the agent of democratic political reform in China in the future?